Etiology of Liver Steatosis Influences the Severity of Ischemia/Reperfusion Injury and Survival After Liver Transplantation in Rats. Issue 11 (25th August 2020) - Miyachi, Yosuke; Yagi, Shintaro; Hirata, Masaaki; Iwamura, Sena; Yao, Siyuan; Shirai, Hisaya; Okumura, Shinya; Iida, Taku; Ito, Takashi; Uozumi, Ryuji; Kaido, Toshimi; Uemoto, Shinji
Abstract : Liver steatosis is a leading cause of graft disposal in liver transplantation, though the degree of steatosis is often the single factor determining acceptability of the graft. We investigated how the cause of liver steatosis affects graft function in rat orthotopic liver transplantation (OLT). OLT was performed using 2 types of steatotic liver grafts: the fasting and hyperalimentation (FHA) model and the methionine‐ and choline‐deficient diet models. The FHA and 4‐week feeding of a methionine‐ and choline‐deficient diet (MCDD4wk) groups showed similar liver triglyceride levels without signs of steatohepatitis. Therefore, the 2 groups were compared in the following experiment. With 6‐hour cold storage, the 7‐day survival rate after OLT was far worse in the FHA than in the MCDD4wk group (0% versus 100%, P  = 0.002). With 1‐hour cold storage, the FHA group showed higher aspartate aminotransferase and alanine aminotransferase levels and histological injury scores in zones 1 and 2 at 24 hours after reperfusion than the normal liver and MCDD4wk groups. Intrahepatic microcirculation and tissue adenosine triphosphate levels were significantly lower in the FHA group after reperfusion. Hepatocyte necrosis, sinusoidal endothelial cell injury, and abnormal swelling of the mitochondria were also found in the FHA group after reperfusion. Tissue malondialdehyde levels were higher in the MCDD4wk group before and after reperfusion. However, the grafts up‐regulated several antioxidant enzymes soon after reperfusion. Even though the degree of steatosis was equivalent, the 2 liver steatosis models possessed quite unique basal characteristics and showed completely different responses against ischemia/reperfusion injury and survival after transplantation. Our results demonstrate that the degree of fat accumulation is not a single determinant for the usability of steatotic liver grafts.